Notch Signaling Activates Yorkie Non-Cell Autonomously in Drosophila - Graves, Hillary K.; Woodfield, Sarah E.; Yang, Chih-Chao; Halder, Georg; Bergmann, Andreas (PLOS ONE, 2012)
In Drosophila imaginal epithelia, cells mutant for the endocytic neoplastic tumor suppressor gene vps25 stimulate nearby untransformed cells to express Drosophila Inhibitor-of-Apoptosis-Protein-1 (DIAP-1), conferring resistance to apoptosis non-cell autonomously. Here, we show that the non-cell autonomous induction of DIAP-1 is mediated by Yorkie, the conserved downstream effector of Hippo signaling. The non-cell autonomous induction of Yorkie is due to Notch signaling from vps25 mutant cells. Moreover, activated Notch in normal cells is sufficient to induce non-cell autonomous Yorkie activity in wing imaginal discs. Our data identify a novel mechanism by which Notch promotes cell survival non-cell autonomously and by which neoplastic tumor cells generate a supportive microenvironment for tumor growth.